THE STATE INFLUENCE ON ECONOMIC INTERESTS AND VECTOR OF ACTIONS OF ECONOMY SUBJECTS IN THE PROCESS OF STRATEGY FORMATION - E. E. Bydtaeva (Publishing House of the State University of Management, 2020)
The need of the state influence on interests and preferences of economy subjects has been proved; options of the mechanism of influence of interests of the state and the subject of economy on a vector of actions of the last have been considered; substantial distinctions of methods of state influence on the economy subjects have been disclosed; requirements to the elements making the basis of the strategy of development have been concretized. Results of the conducted research can be used in the process of forming the strategy of economic development. It has been concluded that at the stage of formation of the economic development strategy, the dominance of the interests of the state can be ensured by it in relation to a separate category of economy subjects; the state can exercise influence on the interests of other economy subjects in the form of a «declaration of intent».